Effects of the inclusion of tannins in beef cattle grazing supplements on the dry matter in situ degradability (Research, Society and Development, 2020)
The objective of this study was to evaluate the effect of the inclusion of tannin in the supplementation of pasture cattle on dry matter degradability. Two male Nellore bovines, non-castrated, cannulated in the rumen, and supplemented with protein-energetic supplement with 26% crude protein (CP) at 0.5% of body weight, containing 1g in the diet of one of the animals were used. of tannin tannin per kg of dry matter (DM). DM degradation of DDG samples (which means dry grains by distillation), soybean meal and corn was evaluated. For all foods there was no significant difference between treatments. The DDG showed an indigestible fraction (65.6%) greater than the potentially digestible fraction (20.5%), the potentially degradable fraction of DM (B0) of soybean meal was lower than that observed in the literature, however the rate of degradation of fraction B0 (0.037) was similar (0.080). The best fit of the disappearance models for corn DM was with separate treatments. However, there was no significant difference between them. The degradation rate of the tannin treatment (0.178) is not reliable because it includes zero within the confidence interval. There is a significant difference only in the half-life, and it is possible to observe that treatment with tannin takes almost twice as long (96.35%) to digest half of the potentially digestible fraction of treatment without tannin.